Effects of Shelling Ratio and Particle Characteristic on Physical Properties of Three-Layered Particleboard Made from Different Wood Species - Muhammad Navis Rofii; Satomi Yumigeta; Shigehiko Suzuki; Tibertius Agus Prayitno (Masyarakat Peneliti Kayu Indonesia, 2013)
Wood waste materials such as flakes, particles, sawdust, planer shaving, which are residues from furniture industry can be utilized to manufacture many composites such as particleboard. The most commonly used particleboard has three layers: two face layers and one core layer. The face layers consist of fine particles and the core layer is made of coarse particles.This study aimed to show the effect of shelling ratio and particle characteristic on physical properties of three-layer particleboard with high density core and different particles on surface layers. The materials used in this study were hinoki (Chamaecyparis obtusa) strand and knife-milled Douglas-fir (Pseudotsuga manziesii) as surface layers and hammer-milled matoa (Pometia sp.) as core layer. The wood particles were collected from a wood company. Adhesive used was MDI resin (methylene diphenyl diisocyanate) with 6 % content in mat preparation. The pressing conditions were: temperature 180°C, pressure 3 MPa and pressing time 5 min. The target density was 0.72 g/cm3 with board size of 340 mm x 320 mm x 10 mm. Factors used in this study were layer structure according to board shelling ratio and particle characteristic. The parameters of this study were density, moisture content, thickness swelling, water absorption, linear expansion and vertical density profile.The results of this study indicate that all boards meet the requirements of JIS A 5908-2003. Higher shelling ratio of surface layers resulted in higher physical performance of three-layer particleboard. In terms of particle type, hinoki strands showed the best performance in board density and linear expansion, while Douglas-fir particle showed the best performance in moisture content, thickness swelling and water absorption. Improvement of physical properties of particleboard with high density wood particles in core layer can be conducted by adding surface layer with higher quality wood particles such as hinoki strands or Douglas-fir particles. Compared to Douglas-fir particles, hinoki strands as surface layers contribute to higher enhancement of three-layer particleboard with matoa as the core layer.